Analisa dan Perancangan Sistem Informasi Eksekutif Pengukuran Kinerja Karyawan STMIK STIKOM Bali - M Samsudin (Media Aplikom, 2018)
The quality of Human Resources (HR) is one of the factors to improve the productivity performance of the institution. Human Resources is required which have high competence skill or competence to be able to support the achievement of employee performance. STMIK STIKOM Bali measurement and evaluation of employee performance annually. The problem now facing is the employee performance review process is still subjectivity in the decision. In this research, analysis and designed an executive information system for employee performance measurement can be used to evaluate employees. The method of research conducted in this study is from the collection of data, literature, system analysis and system design. Concept planning and design of the system is done with Context analysis diagrams, Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD).